Frontline Care in Irish Intellectual Disability Services: The Contribution of Nurses and Non-Nurse Care Staff - SHEERIN, FINTAN (My University, 2008)
The ongoing development of generic intellectual disability services in Ireland, driven by a policy of inclusion and normalisation, has posed significant challenges to the interdisciplinary team, with the creation of new frontline carer roles not linked to any particular profession. It is within this context that attention has been focused on the appropriateness of nursing to frontline caring in intellectual disability service provision. The separation of caring and nursing posts that is now evident within many residential services suggests that decisions have already been made regarding the appropriateness of nursing within particular settings. These decisions have, however, been made in the absence of any real attempt to delineate the contribution of nursing to frontline caring in Ireland. This study is the first of its type in Ireland and seeks to set out the unique interventional contribution of nursing and non-nurse caring within frontline intellectual disability services.
PUBLISHED
Keywords: Intellectual Disability; Nursing; Frontline caring; Social care; Inclusive Society; Making Ireland